2010
DOI: 10.1021/ol902833p
|View full text |Cite
|
Sign up to set email alerts
|

General Methodology for the Preparation of 2,5-Disubstituted-1,3-oxazoles

Abstract: Deprotonation of 2-(phenylsulfonyl)-1,3-oxazole (1) readily provides a useful C-5 carbanion which is reactive with a variety of electrophiles. Aldehydes and ketones are useful substrates, and the formation of 5-iodo- and 5-tri-n-butylstannyl oxazoles affords access to cross-coupling reactions. Subsequent nucleophilic displacement of the 2-phenylsulfonyl group provides a general route for the synthesis of 2,5-disubstituted-1,3-oxazoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Owing to the important applications of oxazole derivatives, various synthetic methodologies for these compounds have been reported. Generally, the procedures for the synthesis of oxazoles include the cyclodehydration of acyclic precursors [12][13][14][15][16], the oxidation of oxazolines [17][18][19] and the coupling of the prefunctionalized oxazoles with organometallic reagents [20][21][22]. In light of these applications, the development of milder and more general procedure to access oxazoles is still desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the important applications of oxazole derivatives, various synthetic methodologies for these compounds have been reported. Generally, the procedures for the synthesis of oxazoles include the cyclodehydration of acyclic precursors [12][13][14][15][16], the oxidation of oxazolines [17][18][19] and the coupling of the prefunctionalized oxazoles with organometallic reagents [20][21][22]. In light of these applications, the development of milder and more general procedure to access oxazoles is still desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, diversely substituted bromooxazoles were reported as multipurpose building blocks for various transformations, including:• palladium-catalyzed Negishi reactions, [31,32] Suzuki-Miyaura, [31][32][33][34][35][36][37][38][39][40][41][42] Stille, [31][32][33][34][35] and including sp 3 -sp 2 cross-coupling, [36] Heck reaction with alkenes and alkynes; [37] Buchwald-Hartwig amination, [38] alkoxylation [38] and aminocarbonylation. The method was optimized, and its scope was extended to all three isomeric parents, as well as various alkyl-and aryl-substituted bromooxazoles.…”
mentioning
confidence: 99%
“…Subsequent reactions for displacement of the 2-(phenylsulfonyl) group have established a general route to 2,5-disubstituted-1,3-oxazoles 11. Prior literature reveals relatively little information regarding useful methods for C-4 and C-5 halogenation of oxazoles 12.…”
mentioning
confidence: 99%
“…Prior literature reveals relatively little information regarding useful methods for C-4 and C-5 halogenation of oxazoles 12. However, the well-behaved carbanion from 7 (Scheme 3, R = SO 2 Ph, X = Li) facilitates convenient halogenation and stannylation reactions yielding 9 and 10 , respectively 11. Furthermore, we have shown that 5-bromo-2-(phenylthio)-1,3-oxazole ( 8 ) undergoes a facile base-induced isomerization, characterized as a halogen dance rearrangement to provide access to the 4-bromo-1,3-oxazole 11 (85%) 13.…”
mentioning
confidence: 99%